Effect of IL-35 on soluble CD40 ligand-induced injury of vascular endothelial cells - LI Ming, SUN Hai-ling, LIU Juan-li, GUO Wei-wei (Jichu yixue yu linchuang, 2022)
Objective To investigate the concentration of soluble CD40 ligand (sCD40L) and interleukin (IL)-35 in peripheral blood of patients with deep vein thrombosis (DVT), and to study the protective effect of IL-35 on sCD40L-induced vascular endothelial cell injury. Methods Peripheral venous blood 3 mL was collected respectively from 30 patients with acute deep vein thrombosis patients (DVT group) and 30 healthy controls (HC group). Enzyme-linked immunosorbent assay (ELISA) was used to detect the level of serum IL-35, sCD40L, IL-1β, and IL-18. Human umbilical vein endothelial cells (HUVECs) were cultured and divided into three groups: control group (phosphate buffer), sCD40L group (25 μg/mL sCD40L), and IL-35 group (20 ng/mL IL-35 and 25 μg/mL sCD40L). CCK8 kit was used to detect the viability of HUVECs and ELISA was used to detect the level of IL-1β and IL-18 in the cell culture supernatant. The protein expression of GSDMD-N and cleaved caspase-1 in HUVECs was detected by Western blot. Results The level of IL-35 in peripheral blood of DVT patients was signifi- cantly lower than that in HC group, while the level of sCD40L, IL-1β, and IL-18 was significantly higher(P＜0.05). Furthermore, there was a negative correlation between IL-35 and sCD40L in DVT patients. In vitro, IL-35 inhibited the damage of cells viability induced by sCD40L, and reduced the concentration of IL-1β and IL-18 in culture supernatant from sCD40L group. The protein expression of GSDMD-N and cleaved caspase-1 in cells was decreased too. Conclusions The level of IL-35 in peripheral blood of DVT patients is decreased, while the level of sCD40L is increased. IL-35 has a protective effect on sCD40L-induced vascular endothelial cell injury, which may have some impacts on the pathogenesis of thrombosis.